2020
DOI: 10.3390/molecules25204724
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Peptide–GPCR Interactions and Their Dynamics

Abstract: Many biological functions of peptides are mediated through G protein-coupled receptors (GPCRs). Upon ligand binding, GPCRs undergo conformational changes that facilitate the binding and activation of multiple effectors. GPCRs regulate nearly all physiological processes and are a favorite pharmacological target. In particular, drugs are sought after that elicit the recruitment of selected effectors only (biased ligands). Understanding how ligands bind to GPCRs and which conformational changes they induce is a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 335 publications
(465 reference statements)
0
32
0
Order By: Relevance
“…Another unresolved challenge is understanding the impact of ligand dynamics on receptor activation, in particular for peptide-activated GPCRs (reviewed in Ref. [182]). There is a growing body of evidence from NMR studies and 3DVA of cryo-EM data that peptide ligands can sample multiple conformations when bound to a receptor [183][184][185][186].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Another unresolved challenge is understanding the impact of ligand dynamics on receptor activation, in particular for peptide-activated GPCRs (reviewed in Ref. [182]). There is a growing body of evidence from NMR studies and 3DVA of cryo-EM data that peptide ligands can sample multiple conformations when bound to a receptor [183][184][185][186].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Cross-linking ncAAs have been widely applied to GPCR studies (reviewed in Ref. [81]) and most recently to arr-GPCR interaction studies. Gagnon et al [82] incorporated the photo-activatable ncAA p-azido-phenylalanine (Azi) into the intracellular domains of the angiotensin II receptor type 1 (AT 1 R).…”
Section: Mapping the Arrestin-gpcr Interaction Surface Via Cross-linkingmentioning
confidence: 99%
“…Cross‐linking ncAAs have been widely applied to GPCR studies (reviewed in Ref. [81]) and most recently to arr–GPCR interaction studies. Gagnon et al .…”
Section: Identifying Functional Hot Spots Of Arrestin By Mutagenesismentioning
confidence: 99%
“…In terms of structure, GPCRs are characterized by an extracellular N-terminus, followed by seven transmembrane α-helices connected by three intracellular and three extracellular loops and finally an intracellular C-terminus. These receptors undergo conformational changes that facilitate the binding and activation of multiple effectors [ 100 ]. In this field, Caporale et al reported a hierarchical approach based on the hypothesis that a stable, amphipathic α-helix of the N-terminal fragment of the parathyroid hormone was a prerequisite for the binding and activation of its receptor (PTH1R).…”
Section: Peptides As “Tools” For (Bio)supramolecular Interactionmentioning
confidence: 99%